Analysis Study Utilization Source Studying History at State High Schools in Magelang City 2013 Curriculum - Radityo, Sri; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2019)
This research aims to explore the phenomenon of history learning sources utilization in SMA Negeri schools in Magelang, focusing on several key issues: the knowledge and understanding of history teachers regarding these sources, how teachers at SMA Negeri 1 Magelang and SMA Negeri 2 Magelang utilize them, and the difficulties they encounter in the classroom. Utilizing qualitative research methods through a case study approach, the study was conducted at SMA Negeri 1 Magelang and SMA Negeri 2 Magelang. Data were collected using a combination of observation, interviews, and documentation. The findings reveal that history teachers at both schools know the various types and kinds of history learning sources available. However, the extent and manner of their utilization vary, with teachers often opting for the most easily managed and comprehended sources. This preference highlights a pragmatic approach to teaching, where ease of use and accessibility of learning materials play a significant role in their integration into the classroom. Despite this, challenges remain in effectively incorporating a diverse range of history learning sources, pointing to a need for further support and resources to help teachers fully leverage these educational tools in their teaching practices.